2011
DOI: 10.1074/jbc.m111.269753
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Amino Acids Disturb Xylanase Thermostability and Activity

Abstract: Background: Unlike the ␣-helix/␤-strand, the non-regular region contains amino acid defined as disordered residue (DR); its effect on enzyme structure and function is elusive. Results: Terminal DR deletions significantly increased xylanase thermostability and activity. Conclusion: Terminal DRs disturb xylanase thermostability and activity. Significance: DR deletion increased regular secondary structural content, and hence, led to slow decreased ⌬G 0 in the thermal denaturation process, and ultimately, enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 41 publications
(47 reference statements)
1
43
1
Order By: Relevance
“…Previous reports indicated that N-terminal region and hydrogen bond network of xylanase played crucial roles in its thermo-stability8915. GH11 xylanases of thermophilic origin generally have longer N-terminal region compared to mesophilic ones, indicating its role on enhancing the thermo-stability3940. Several attempts have been made to enhance the thermo-stability of xylanase by substituting the N-terminal region of various non-thermostable xylanases with those of thermostable xylanases8.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that N-terminal region and hydrogen bond network of xylanase played crucial roles in its thermo-stability8915. GH11 xylanases of thermophilic origin generally have longer N-terminal region compared to mesophilic ones, indicating its role on enhancing the thermo-stability3940. Several attempts have been made to enhance the thermo-stability of xylanase by substituting the N-terminal region of various non-thermostable xylanases with those of thermostable xylanases8.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that terminal amino acid residues are crucial for the entire enzyme (42,54). Liu et al have reported that disordered terminal amino acid deletions increased regular secondary structural contents, which led to slow decreases in Gibbs free energy in the thermal denaturation process and ultimately enhanced enzyme thermostability (55). In the present study, circular dichroism (CD) spectrum data showed that the substitution of amino acids at the N terminus of XynA and XynATM1 did not cause secondary structure changes in the proteins (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the deletion of N- and C-terminal (XynΔNC) residues had an opposing effect on Xyn T opt, but had an additive effect on t 1/2 . The analysis of terminal DRs using a model structure of Xyn showed that the new N- and C-terminals can come closer to each other after the deletion of five N-terminal DRs and one C-terminal DR, suggesting that this close contact between the N- and C-terminal can provide additional compactness to the structure thereby making the deletion mutants more stable than native Xyn (88). More recently, the role of N- and C-terminal contact in the family 10 xylanase BSX was investigated through site-directed mutagenesis to assess protein folding and stability of these mutants under more than one extreme condition (12, 13).…”
Section: N- and C-terminal Contacts And Protein Stabilitymentioning
confidence: 99%